2015
DOI: 10.1038/am.2014.111
|View full text |Cite
|
Sign up to set email alerts
|

Hybridizing wood cellulose and graphene oxide toward high-performance fibers

Abstract: High-performance microfibers such as carbon fibers are widely used in aircraft and wind turbine blades. Well-aligned, strong microfibers prepared by hybridizing two-dimensional (2D) graphene oxide (GO) nanosheets and one-dimensional (1D) nanofibrillated cellulose (NFC) fibers are designed here for the first time and have the potential to supersede carbon fibers due to their low cost. These well-aligned hybrid microfibers are much stronger than microfibers composed of 1D NFC or 2D GO alone. Both the experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
66
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 39 publications
1
66
0
Order By: Relevance
“…The fundamental bottom-up strategy can essentially go beyond 1D building blocks (tubes, wires, filaments) toward 2D building blocks [e.g., atomic layers of graphene oxide (GO), boron nitride, and molybdenum disulfide] and 1D/2D hybrids. For example, it has been recently shown that hybrid microfibers containing well-aligned and mixed 2D GO sheets and 1D CNF fibers are both much stronger and tougher than the microfibers made of pure GO sheets or CNF fibers, due to synergistic enhancement of bonding between GO and CNF fibers (50). These fertile opportunities could lead toward a novel class of engineering materials that are both strong and tough with an array of potential applications, such as lightweight composites, flexible paper electronics, and energy devices.…”
Section: Discussionmentioning
confidence: 99%
“…The fundamental bottom-up strategy can essentially go beyond 1D building blocks (tubes, wires, filaments) toward 2D building blocks [e.g., atomic layers of graphene oxide (GO), boron nitride, and molybdenum disulfide] and 1D/2D hybrids. For example, it has been recently shown that hybrid microfibers containing well-aligned and mixed 2D GO sheets and 1D CNF fibers are both much stronger and tougher than the microfibers made of pure GO sheets or CNF fibers, due to synergistic enhancement of bonding between GO and CNF fibers (50). These fertile opportunities could lead toward a novel class of engineering materials that are both strong and tough with an array of potential applications, such as lightweight composites, flexible paper electronics, and energy devices.…”
Section: Discussionmentioning
confidence: 99%
“…But they claimed that this value is much higher than those reported in other literature. Also Li et al (2015) combined graphene oxide (GO) nanosheets and nanofibrillated cellulose for use in high-performance device applications to replace traditional high-performance synthetic fibres, such as the carbon fibres used mostly in the aviation industry and in wind turbine blades. They reported that GO nanosheets have several hydroxyl, carboxyl, and epoxide functional groups on their basal plane and edges, strengthening the bonding in the material and giving the GO nanosheets good dispersion in water.…”
Section: Introductionmentioning
confidence: 99%
“…Then the gel fiber was pulled out and dried under tension at room temperature. The shear force introduced through extruding, and the tension applied during drying caused the building blocks to align along the fiber length direction, leading to a highly aligned microfiber . Good flexibility was demonstrated by making knots readily by hand, as shown in Figure b.…”
mentioning
confidence: 99%
“…For comparison, we also simulate the sliding of the top and bottom CNT layers relative to the middle NFC layer in the CNT–NFC–CNT not aligned model. Recent studies on tensile failure of cellulose nanopaper (made of a network of NFC nanofibers) and cellulose–graphene oxide hybrid fiber reveal that, due to the facile formation nature of hydrogen bonds, the inter‐fiber sliding involves a cascade of events of forming, breaking, and reforming of hydrogen bonds in between neighboring NFC nanofibers. Each hydrogen bond breaking dissipates energy.…”
mentioning
confidence: 99%